Using a Wavelet Based Method for High Resolution Satellite Image Fusion - Ali, Hussain (Iraqi Journal of Science, 2024)
The number and quality of commercially available multispectral sensors and thedata they provide are continually improving, but there is always compromisebetween achieving high spatial resolution, necessary for those applications thatrequire high degree of detail, and high spectral resolution when a better featurediscrimination level is needed. However, there are some situations thatsimultaneously require high spatial and spectral resolutions in a single image. Thetechniques of data fusion, or data merging, provide an alternative to that constraint,being used to combine low-resolution multispectral satellite imagery with higherresolution panchromatic or radar imagery, improving their visual quality andinterpretability. Many algorithms and software tools have been developed for fusingpanchromatic and multispectral datasets in remote sensing. Wavelet techniques areincreasingly being used for the processing of images. The algorithm used in thispaper was based on multiresolution wavelet decomposition. The image isdecomposed into multiple channels based on their local frequency content, obtainingnew images each one of them with different degree of resolution. A simple WaveletTransform is used, which is implemented in the ERDAS Imagine Software packagever. 9.2. The procedure was based upon the wavelet transform is to improve thespectral quality of high resolution image acquired by LANDSAT 7 ETM+.